Memupuk Nasionalisme Dalam Industri Pertahanan - Manan Manan; Gathut Imam Gunadi; George Royke Deksino (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstrakDalam mewujudkan komitmen dalam membangun kapabilitas dalam bidang pertahanan, Indonesia melakukan berbagai upaya dalam menetapkan sasaran pokok jangka panjang untuk membangun kemandirian industri pertahanan. Salah satu upaya yang dilakukan adalah menerbitkan UU no. 16 Tahun 2012 tentang Industri Pertahanan. Tidak hanya itu saja, Pemerintah juga sudah membentuk Komite Kebijakan Industri pertahanan atau sering disebut dengan KKIP yang bertugas mewujudkan kemandirian Industri pertahanan yang menghubungkan kedua belah pihak yang mmbutuhkan yaitu Alpalhankam dan bagian pengembangan industri strategis dalam negeri. Nasionalisme dalam bidang Industri pertahanan mempunyai kemampuan memproduksi Alpalhankam yang tidak bergantung pada negara lain merupakan target pemerintah Indonesia dalam bidang industri pertahanan yang ada di Indonesia. Meskipun demikian, masih terdapat beberapa tantangan dalam pemenuhan kebutuhan militer dengan melihat kapasitas industri pertahanan yang ada di Indonesia. Salah satu strategi lainnya adalah dengan membangun dan menanamkan nilai nasionalisme dalam industri pertahanan sehingga upaya tersebut dapat membangun industri pertahanan nasional yang tidak hanya mengembangkan Alpalhankam melalui pengadaan namun juga melalui pemberdayaan industri pertahanan dengan cara penanaman rasa nasionalisme dan bela negara.Kata Kunci: Nasionalisme, Industri Pertahanan, AlpalhankamÂ AbstractIndonesia is currently trying to realize its commitment to building defense capabilities by setting long-term main goals to build the independence of the defense industry. In addition to issuing Law no. 16 of 2012 concerning the Defense Industry, the government also established the Defense Industry Policy Committee (KKIP) which is tasked with realizing the independence of the defense industry by bridging the needs of Alpalhankam and the development of domestic strategic industries. The military embargo imposed by the United States from 1995 to 2005 has made the Indonesian government aware of the importance of the nationalism of strategic industries for the defense system. The nationalism of the defense industry or the ability to produce its defense and security equipment without relying on other countries is one of the targets of the Indonesian government in the defense sector. Nevertheless, there are still some challenges in meeting military needs with the capacity of the defense industry. One strategy in responding to these challenges is to build and instill the values of nationalism in the defense industry so that efforts to empower the national defense industry will not only develop defense equipment through procurement but also through empowering the defense industry by inculcating the values of nationalism in the people involved. in the whole process of activities in the defense industry to state revenue.Keywords: Nationalism, Defense industry, Alpalhankam.